Meningkatkan Kreativitas Guru TK dalam Pembuatan Alat Peraga dari Barang Bekas Melalui Bimbingan Kelompok di TK Negeri 2 Kelubagolit - Tarsisia Dai Kiti (Literasi: Jurnal Pendidikan Guru Indonesia, 2022)
The purpose of this research is to increase the creativity of Kindergarten teachers in the Kelubagolit District for the 2019/2020 Academic Year in making teaching aids with used goods. The data are in the form of interview transcripts and the results of portfolio assessments sourced from the teacher. This type of research is School Action Research (PTS) which is conducted in two cycles. Data was collected using Interview, Portfolio and observation techniques. Data were analyzed using comparative descriptive. Based on the results of School Action Research (PTS) it can be concluded that group guidance can increase teacher creativity in making teaching aids from used goods. The teacher showed his skills and creativity in making teaching aids from used goods, especially after receiving group guidance from researchers. These results were obtained by researchers from observations when conducting interviews and group guidance in making teaching aids from used goods to eleven kindergarten teachers in the Kelubagolit District. It can be proven from the results of observations that there is an increase in teacher creativity from cycle to cycle. In pre-cycle conditions, only 9% of teachers showed good creativity, then in cycle I the percentage of teachers' ability to show creativity well was 46% and increased in cycle II to 82%.